The natural history of monoamniotic twin pregnancies: a case series and systematic review of the literature. (8th January 2015) - Prefumo, Federico; Fichera, Anna; Pagani, Giorgio; Marella, Daria; Valcamonico, Adriana; Frusca, Tiziana
Abstract Objective To describe the natural history of monoamniotic twin pregnancies in contemporary practice. Method Cohort study of monochorionic monoamniotic twin pregnancies with two live fetuses diagnosed at less than 16 weeks and prospectively followed up between 2004 and 2013. A systematic review of the literature using Medline, Embase and Scopus to determine the perinatal mortality rate after 24 weeks of gestation in monoamniotic twins was also performed. Results Twenty pregnancies were analyzed. Four were terminated (in three cases as a result of fetal abnormalities). Another six miscarried spontaneously. Among ten pregnancies reaching viability, there was double intrauterine death in one, and both fetuses were alive at delivery in the other nine. There were no neonatal deaths. Overall survival for fetuses alive at the initial scan was 18/40 (45%; 95% CI 29 to 62%). At meta‐analysis of 13 studies (including the current series), the perinatal mortality rate after 24 weeks was 4.5% (95% CI 3.3 to 5.8%). Conclusions Despite early diagnosis and intensive monitoring, of those fetuses alive before 16 weeks less than half survive until the neonatal period. Most losses are attributable to fetal abnormalities and spontaneous miscarriage and are therefore unlikely to be reduced by further improvements in fetal assessment and monitoring. © 2014 John Wiley & Sons, Ltd.